PENGARUH PENGGUNAAN MEDIA PAPAN BERPAKU (GEOBOARD) TERHADAP HASIL BELAJAR SISWA KELAS 3 MATA PELAJARAN MATEMATIKA DI SD NEGERI 1 SUMBERBULU - Ade Aprilia; Kurniyatul Faizah; Sudarsri Lestari (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2022)
The purpose of this study is to determine the influence of nailed board media (Geoboard) on the mathematics learning outcomes of grade III students at SD Negeri 1 Sumberbulu and to explain the use of nailed board media (Geoboard) on efforts to improve mathematics learning outcomes of grade III students at SD Negeri 1 Sumberbulu. This type of research is Quantitative with Pre-Experimental Design in the form of one group pretest-posttest. Data collection techniques use observation, interviews and tests in the form of achievement tests that aim to measure the achievement of someone who has learned something. The test instruments given have passed the validity test, reliability test, difficulty level and differentiability. Data analysis techniques in this study include prerequisite tests containing normality tests and homogeneity tests as well as Paired sample tests as hypothesis tests. The results of this study show that the use of nailed board media can improve student learning outcomes. This improvement can be seen from the results obtained in pretest and posttest testing. In the implementation of the pretest, the average score of 50 rose to 70 during the posttest, and in the results of the paired samples test, the sig value of 0.000 was less than 0.05, then Ha was accepted which means that the board media has a real effect on the learning outcomes of mathematics subjects of grade III students at SDN 1 Sumberbulu. The success of the process is shown by the increased enthusiasm of students when taking mathematics lessons. In addition, the use of nailed board media can help teachers in delivering the material and make the classroom atmosphere more lively because students are directly involved in learning by freeing students to form flat buildings according to their wishes. This is felt to be quite satisfactory for teachers and researchers. From the results of this research and discussion, it is known that flat building learning using nailed board media can improve mathematics learning outcomes for grade III students of SDN 1 Sumberbulu. Keywords: Nailed board media, Mathematics Learning, Learning outcomes